Exploring students' perspectives from two Canadian dental schools toward online learning experiences - Maragha, Tala; Dempster, Laura; Shuler, Charles; Lee, Vincent; Mendes, Vanessa; von Bergmann, HsingChi (Journal of dental education, 2023)
The utilization of online teaching and learning in dental education has grown during the past two academic years. In addition to its numerous advantages, the modality also has its limitations. The objective of this qualitative study was to explore the perceptions of oral health sciences students at the University of British Columbia (UBC) and the University of Toronto (UofT) regarding their experiences with online learning over the course of 2 pandemic-impacted years. Interpretive Description was used as a methodology to guide semi-structured data collection. Individual interviews and focus groups were conducted with graduate and undergraduate dental and dental hygiene students at UBC and UofT. Qualitative data were coded and analyzed using a thematic approach. A total of 31 interviews and 4 focus groups were conducted. Online teaching and learning demonstrated many advantages, including flexibility, sustainability of curricular content, and promoting inclusivity in the classroom. Students indicated that due to online learning, there were opportunities to gain resources in practicing self-care and additional time to connect with family. Reported limitations of online classrooms included the loss of attentiveness, challenging content, and logistical challenges. Isolation and physical symptoms experienced in online classrooms with prolonged screen times were described as potential threats. The results of this study call for developing a structured and sustainable blended approach that balances the limitations of online classrooms with the interaction and engagement of in-person classrooms and patient care experiences. Based on the students' perspectives toward online learning, a road map was provided to dental educators to consider when designing future dentistry curricula.